Republic of Niger : 2012 Public Expenditure Review - World Bank (Washington, DC, 2014)
The Government's Plan for Economic and Social Development (PESD) 2012-2015 outlines an ambitious public expenditure program to foster sustainable inclusive growth and to improve public service delivery. The 2012 Public Expenditure Review (PER) is the first in a planned series of annual PERs (APERs). The objective of APERs is to provide decision makers in the Nigerien government, domestic stakeholders, as well as Niger's development partners with regular information and analysis on budgetary developments. The APER process aims to meet information requirements of interested stakeholders while minimizing the transaction cost for government. In the absence of a regularly published APER, the authorities are confronted with frequent and often duplicative requests for information, which claim significant staff time in an already very capacity constrained public sector environment. It is envisaged that a "one assessment - one process" approach will help to reduce transaction costs for government while meeting information requirements of interested stakeholders. The APERs will consist of three main parts. The first part will monitor public expenditure performance and the implementation of public financial management reforms. The second part will focus on sectoral public expenditure issues, and the third part will analyze selected public expenditure issues in detail. In the context of the annual PER process, every second year a public expenditure and financial accountability (PEFA) will be carried out. Public expenditure management reform action plan has been adopted in 2012 and provides a road map for reforms and helps coordinate donor support in this area. The Bank is supporting the strengthening of public financial management systems through a technical assistance grant. This PER covers the following topics: introduction in the first chapter. The review's macroeconomic context in the second chapter, an assessment of public expenditure trends and composition in the third chapter, and a review of the volume, modalities, and allocation of official development assistance in the fourth chapter. Public expenditure developments in the health, education, and rural development sectors are reviewed in the fifth, sixth, and seventh chapters, respectively. At the end, chapter eight focuses on strengthening Niger's public expenditure review process.